Exploring Pragmatic Strategies in Energy Drink Advertisements: A Comparative Gricean Analysis of Pakistani and Indian Sting Ads - Khushbakhat Ejaz; Zehra Batool; Danish Sarfaraz (Wah Academia Journal of Social Sciences, 2025)
The marketing of energy drinks in the global markets is often based on dramatic and hyperbolic messages targeting the youthful consumers in the fast-growing markets in regions like Pakistan and India. This paper has used comparative pragmatic and multimodal study of ten advertisements of Sting energy drinks; five advertisements of Sting energy drinks in Pakistan and five advertisements of Sting energy drinks in India. Based on an interpretivist paradigm and a qualitative approach, the study explores the relationship between verbal and visual elements and the way in which these elements of communicative messages strategically comply or do not align with the Cooperative Principle introduced by Grice (1975), including the Maxims of Quality, Quantity, Relevance and Manner. The results reveal that both Pakistani and Indian adverts are overly dramatizing, and violate the Maxim of Quality, building on their use of fantastical and hyperbolic imagery to form aspirational meaning. However, Indian adverts are more traditional and more willing to include declarations regarding the health of their products, and are overt in regard to product details, which serves to curb the possibility of misunderstanding and indicates a stronger level of regulatory and corporate accountability. In Pakistani advertisements, however, emphasis is placed more on foregrounded real-life situations and culturally identifiable metaphors, like witches, exam success, and transformation in the workplace, but there is often a lack of disclosure in terms of health, so Pakistani youth viewers are more likely to be ethically troubled. Combining semiotic analysis (Barthes, 1977; Kress and van Leeuwen, 2006), with Relevance Theory (Sperber and Wilson, 1995), the paper contends that seemingly irrelevant or exaggerated visual features serve to create cognitive salience and produce implicatures that help advertisements to get remembered and persuade audiences. Such comparative analysis would develop a global discourse as it provides a Gricean pragmatics approach to the multimodal advertisement in the South Asian region and, in the process, would explain how the regulatory cultures and repertoires influence pragmatic choices, applied when creating marketing practices of health-sensitive products, that reach younger customers. Policy implications and future work related to the experimental work are outlined.